Pelatihan Regulasi Emosi untuk Menurunkan Kecemasan pada Ibu Hamil di Puskesmas Gondokusuman II Yogyakarta - Dwiyani, Baiq Fira; Widuri, Erlina Listyanti (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2022)
The purpose of this study was to determine the effect of emotional regulation therapy to reduce anxiety in pregnant women, especially in the area of the Gondokusuman II Yogyakarta Public Health Center. The subjects in this study were eight pregnant women who experienced anxiety in the medium and high categories. The data collection method used in this research uses the method of observation, interviews, group discussion forums, and measurements are carried out using quantitative methods, namely by measuring pre and post-test using an anxiety scale in pregnant women. The data analysis technique used a mix of methods, namely quantitative and qualitative methods. Data analysis with quantitative methods was carried out by giving pre and post-tests, while qualitative methods were carried out based on the therapeutic process carried out. The results showed a decrease in the level of anxiety both quantitatively and qualitatively. The qualitative results show that the research subjects are able to recognize the emotions they feel, are able to manage their emotions and control the anxiety they experience by applying relaxation techniques. While the quantitative results show a value of -2.521 with a significance level of 0.012 (<0.05), which means that there is a significant change in the anxiety level score before and after being given training on emotion regulation and relaxation techniques. Based on the results of the study, it can be concluded that emotional regulation training can reduce anxiety levels in pregnant women in the Gondokusuman II Health Center area.